Assessment of the Effectiveness of Internet-Based Distance Learning through the VClass e-Education Platform - Pukkaew, Chadchadaporn (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This study assesses the effectiveness of internet-based distance learning (IBDL) through the VClass live e-education platform. The research examines (1) the effectiveness of IBDL for regular and distance students and (2) the distance students’ experience of VClass in the IBDL course entitled Computer Programming 1. The study employed the common definitions of evaluation to attain useful statistical results. The measurement instruments used were test scores and questionnaires. The sample consisted of 59 first-year undergraduate students, most of whom were studying computer information systems at Rajamangala University of Technology Lanna Chiang Mai in Thailand. The results revealed that distance students engaged in learning behavior only occasionally but that the effectiveness of learning was the same for distance and regular students. Moreover, the provided computer-mediated communications (CMC) (e.g., live chat, email, and discussion board) were sparingly used, primarily by male distance students. Distance students, regular students, the instructor, and the tutor agreed to use a social networking site, Facebook, rather than the provided CMC during the course. The evaluation results produce useful information that is applicable for developing and improving IBDL practices.